Analisis Peran Dana Alokasi Khusus (DAK) Fisik Dalam Meningkatkan Indeks Pembangunan Manusia (IPM) dan Pertumbuhan Ekonomi Provinsi Sumatera Utara - Ridha Maysaroh; Muhammad Arif (El-Mujtama: Jurnal Pengabdian Masyarakat, 2022)
This study aims to describe how the role of physical regional special allocation funds (DAK) in increasing the human development index (IPM) and economic growth in the province of North Sumatra. This study uses a library research approach with data sources used in the form of books, magazines and websites that are relevant to the research topic. The data collection technique in this research is documentation, which is looking for data about things or variables in the form of notes, pictures, books, papers or articles and journals. The results of the study indicate that a well-managed and targeted DAK will improve the Human Development Index (IPM). A good Human Development Index (HDI) will encourage economic growth, especially in DAK in North Sumatra Province. This is because if DAK is managed by the government properly it can improve the quality of education, health services, can reduce damage to infrastructure and so on in the area. The Physical Special Allocation Fund (DAK) is a fund sourced from the APBN which is allocated to certain regions to help fund special activities in the region and in line with national priorities, in particular to finance the needs for basic public service facilities and infrastructure that have not yet reached certain standards. The amount of DAK allocation in each region is determined by index calculation based on general criteria, special criteria, and technical criteria. Meanwhile, to become a national priority, the regional government's work plan must also be included in the government's work plan for the relevant fiscal year. With the existence of a special allocation fund, it can support the level of the Human Development Index (IPM) through community services, health services, infrastructure development and infrastructure in the regions which indirectly affect the welfare of the community itself. Keywords: Special Allocation Fund, Human Development Index, Economic Growth